Claims data-based analysis of the influence of individual and regional characteristics on the utilisation of long-term care by people with dementia in Baden-Wurttemberg, Germany - Forstner, Johanna; Wensing, Michel; Koetsenruijter, Jan; Wronski, Pamela (BMC geriatrics, 2019)
Challenges of future dementia care include increasing shortage of qualified healthcare providers and decreasing potential of informal care by relatives. In order to meet those challenges, changes in dementia care are needed. These changes should be based on data of both care utilisation and care supply. The aim of this study was to provide insight into individual and regional characteristics that influence the utilisation of long-term care by people with dementia. The study was a retrospective cross-sectional analysis of claims-based data and other available data referring to one index year. All data were aggregated for small geographic districts. The study population comprised people with a dementia diagnosis, 65 years and older in Baden-Wuerttemberg and insured by the largest health insurer. Utilisation of nursing home care, informal care, and respite care was analysed using binary coded logistic multilevel analyses. Seventy nine thousand three hundred forty-nine people with dementia were included in the analyses. Nursing home care was used by 20.4%, informal care by 30.6%, and respite care by 3.5% of people with dementia. Individual characteristics that influence care utilisation included age, sex and the level of care dependency. The utilisation of informal care (OR = 1.713) and respite care (OR = 2.036) was higher in rural districts than in city districts. Respite care supply had an effect on the utilisation of respite care (OR = 1.173). The study found differences between districts in the utilisation of long-term care for dementia. These differences were largely explained by the composition of the population within the districts. An exception was the utilisation of respite care, which was higher in districts which have higher supply. Individual characteristics that influenced care utilisation are age, sex, level of care dependency and, with regard to informal care, comorbidity. Further research should be conducted on a small-area level, include further individual characteristics as well as other care and living forms.
Gesehen am 25.02.2020